Analisis Motivasi Kerja dalam Meningkatkan Kinerja Karyawan Pada Toko Dewi Sri Kabupaten Sumenep - Wardhatul Hasanah; Kurdi, Moh. (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze work motivation in improving employee performance at Dewi Sri Store in Sumenep Regency. The main issues faced are the lack of recognition for work achievements, less conducive working conditions, inadequate reward and incentive systems, and ineffective communication between management and employees. A qualitative approach was used with in-depth interview and direct observation methods. The research results show that employee work motivation is influenced by intrinsic and extrinsic factors. Intrinsic factors include recognition and appreciation as well as training and development, which have been proven to increase employee enthusiasm and performance. Extrinsic factors encompass working conditions, reward and incentive systems, and effective communication between management and employees. This research reveals that consistent recognition, improvement of working conditions, competitive reward systems, transparent communication, and continuous training programs play a significant role in enhancing employee motivation and performance. The implementation of strategies that optimize these factors is expected to create a more productive and harmonious work environment, thereby improving overall employee performance and company success